PERAN INTERNATIONAL LABOUR ORGANIZATION (ILO) MENGATASI PERDAGANGAN MANUSIA PADA KORBAN WANITA DAN ANAK DI BAWAH UMUR DI NEPAL - Yosephine, Agnes Cindy; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study looks at the role of the ILO in helping Nepal address the issue of human trafficking. The study aims to understand how international organizations can contribute to addressing this complex problem. Nepal has a high number of human trafficking victims, and if the issue is not addressed promptly, it will have a negative impact on the country. This study was examined using the theory of the role of international organizations. The data collection process based on this research was conducted using an explanatory qualitative method. The data was mainly sourced from ILO and Nepalese government organizations providing regular contribution reports. The study showed that the ILO plays a role in addressing human trafficking in Nepal from an international perspective without violating state sovereignty or interfering with the Nepalese government's implementation process, by initiating a number of programs such as the Decent Work Programme, Work in Freedom, the Integrated Programme on Fair Recruitment, and the Skills for Employment Project. Keywords: ILO, Human Trafficking, Nepal, Women and Children, Migrants, Forced Labor.